2020
DOI: 10.1099/mic.0.000931
|View full text |Cite
|
Sign up to set email alerts
|

Microbial metabolism of isoprene: a much-neglected climate-active gas

Abstract: The climate-active gas isoprene is the major volatile produced by a variety of trees and is released into the atmosphere in enormous quantities, on a par with global emissions of methane. While isoprene production in plants and its effect on atmospheric chemistry have received considerable attention, research into the biological isoprene sink has been neglected until recently. Here, we review current knowledge on the sources and sinks of isoprene and outline its environmental effects. Focusing on degradation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…There is no obvious reason for the differential capacity for potential isoprene degradation with the the rubber plantation soil, as rubber is a polymer of isoprene, and some bacteria, e.g., Gordonia spp., can degrade both [ 23 ]. From previous studies, there is no evidence of a relationship between plant isoprene production and isoprene consumption in associated soils, probably because soil microbiota primarily consume isoprene produced in the soil, e.g., by bacteria and fungi rather than from the atmosphere [ 15 , 16 ]. Isoprene production from the studied plants has only been documented for oil palm and rubber trees [ 10 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no obvious reason for the differential capacity for potential isoprene degradation with the the rubber plantation soil, as rubber is a polymer of isoprene, and some bacteria, e.g., Gordonia spp., can degrade both [ 23 ]. From previous studies, there is no evidence of a relationship between plant isoprene production and isoprene consumption in associated soils, probably because soil microbiota primarily consume isoprene produced in the soil, e.g., by bacteria and fungi rather than from the atmosphere [ 15 , 16 ]. Isoprene production from the studied plants has only been documented for oil palm and rubber trees [ 10 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soil is a sink for some of this isoprene [ 13 , 14 ]. There is also the potential for internal cycling (both production and consumption) of isoprene within soils [ 15 ], with a range of microbes being responsible for isoprene consumption, such as members of the genera Arthrobacter , Nocardia, Nocardiodes, Rhodococcus, Bacillus, Alcaligenes, Ramlibacter, Variovorax, Klebsiella, Pantoea and Pseudomonas [ 16 ]. Knowing the potential and the capacity of soil bacteria and bacterial communities to consume isoprene will lead to a better understanding of isoprene degradation mechanisms in soil and the global atmospheric isoprene budget.…”
Section: Introductionmentioning
confidence: 99%
“…AD45 from freshwater sediments, which has become a key bacterial strain for the study of isoprene metabolism [43,[58][59][60][61]. Details about the isoprene-degrading strains belonging to these genera are provided in [62]. Finally, to our knowledge, no anaerobic bacteria, archaea, or fungi have been reported to use isoprene as a sole carbon and energy source, although Kronen et al [63] have recently shown that strict anaerobes can use isoprene as an electron acceptor to support homoacetogenesis, and thus anaerobic degradation of isoprene also warrants further attention.…”
Section: Diversity Of Isoprene-degrading Bacteriamentioning
confidence: 99%
“…This is a molecule that I really had very little awareness of, but it is a major volatile hydrocarbon emitted in vast quantities by trees and other vegetation. The authors of the review, Colin Murrell and Andrew Crombie from the University of East Anglia, UK, and Terry McGenity (@TMcgenity), from the University of Essex, UK, point out that this chemical, more formally known as 2-methyl-1,3 butadiene, is produced in the biosphere in quantities of around 500 teragrams (Tg) of carbon per year [2], which is of a similar magnitude to that of methane! The chemical has complex interactions in the atmosphere, being implicated in both warming and cooling events.…”
Section: Full-textmentioning
confidence: 99%